Effect of methane supplementation on the performance, vibration and emissions characteristics of methane-diesel dual fuel engine - Tripathi, Gaurav; Nag, Sarthak; Sharma, Priybrat; Dhar, Atul (Frontiers in Thermal Engineering, 2023)
The increasing energy demands, especially in transportation sector, and the challenges of excess pollution and environmental degradation caused due to the conventional fuels, as well as their limited availability has highlighted the need to look for alternative fuels to sustain future needs. Methane is capable of catering to these demands due to its wide availability, both in renewable and non-renewable energy sources. The present work explores the effect of methane supplementation on the performance and emission characteristics as well as the vibrations in internal combustion engines. A four-stroke compression ignition engine is modified to run as a methane-diesel dual fuel engine where methane is inducted through intake manifold and diesel is directly injected into cylinder. Tests are performed by varying engine load and methane energy levels up to 75%. Our study shows that the participation of methane at lower load conditions is weak due to its higher auto ignition temperature and higher calorific value. The emissions, particularly CO and NO, are observably higher at 75% load conditions due to the efficient combustion and higher temperature at higher load conditions. The vibration studies on the dual fuel combustion indicates that the introduction of methane also suppresses the frequency spectrum of combustion noise and reduces the ringing intensity level of vibration for complete spectrum of engine loads, with the effect being prominent at higher loads. Overall, our results suggests that combustion of methane in dual fuel diesel engine shows distinct characteristics at contrasting load conditions.